The Effect Of Deferred Tax Assets And Deferred Tax Liabilities On Accrual Profit Management In Companies - Susena , Karona Cahya; Damarsiwi , Eska Prima Monique; Hijeria , Putri (Utami Publisher, 2025)
The annual financial report reflects the company's development and has a very important role. Financial reports function as a tool for evaluating company management performance. Earnings management refers to the practice of legitimate manipulation in financial reporting to adjust a company's earnings in accordance with management policy. One factor that can influence earnings management is deferred tax assets. This article aims to analyze the influence of deferred tax assets and deferred tax liabilities on company accrual earnings management. The purpose of this article is to provide an understanding of the relationship between these two variables. The research method used in this article is a qualitative literature review.